Sobre el rol de los vínculos en el filtro Kalman. - Salgado, Ariel O. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2016)
Fil. Salgado, Ariel O.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina